Synthesis, characterization and corrosion studies of polyanailine(PANI)/ceriem dioxide(CeO2) nano composite. (2020) - Shetty, Karthika; Jayadev,; Raj, Kalyan; Mohan, N.
Abstract: The corrosion resistant nature of newly prepared Nano composite (polyaniline-ceria) is focused in this paper. The Cerium oxide nanoparticles were efficiently prepared by a combustion method. PCN was prepared by in-situ polymerization of distilled aniline in the existence of CeO2 nanoparticles. The prepared nanocomposites were characterized by Fourier-transform infrared spectra, X-ray diffraction, Scanning electron microscopy and Thermo gravimetric analysis. The different ratio of PANI-Ceria is mixed with fixed ratio of Araldite as epoxy. The corrosion resistance nature of PANI-Ceria on Steel 316 was studied in 0.25 M HCl solution by employing electrochemical work station. The polarization curve reveals that PCN is a mixed-type inhibitor.